GESTIÓN DE LA INFORMACIÓN EN EL PROCESO COMERCIAL DE UNA EMPRESA VITIVINICOLA - OSORIO GAMONAL, ERICK (2021)
The objective of this thesis is a good commercial administration, for the Vitivinicultural organizations, it will begin with the exploration of the company, trying to find the correct technology, its needs are evaluated in its information operation, highlighting deficiencies; much ignorance is observed in the subjects of information technology. The term ERP is deepened and its optimization in the management of operations for a good decision-making, the benefits, reasons for its fixation and its effect on organizations are sustained. In the first chapter, the company was investigated as to the problems it is going through and the indicators to evaluate the feasibility of the work. In chapter II bibliography and concepts necessary to carry out the plan were checked. In Chapter III, an organization of the time and resources necessary to carry out the plan was achieved. In chapter IV, what was planned was carried out and the plan was monitored and controlled. In Chapter V the plan was closed. In chapter VI the results were evaluated. In the end, their primary processes and needs were analyzed, and this is how the initiative to establish an ERP system in the organization is exposed; demonstrating all the advantages that lead to this conclusion. Keyword: ERP, Viticulture, Commercial Management, Automation.